Redevelopment of library and information services after Tsunami: A comparative study of Aceh and Sri Lanka - Baba, Zawiyah (Persatuan Pustakawan Malaysia, 2009)

(untitled)
Aceh and Sri Lanka were hit by the tsunami in December 2004. This brought about mass destruction to numerous areas in both localities. This paper looks at the rebuilding and redevelopment of the library network in both areas.